Pre- and post-tsunami, urban tourism development in Phuket - Khuadthong, Bussalin; Kasim, Azilah (Routledge, 2020)
Cities of every country play an essential role in driving economic and social development because there are various tourist destinations in urban areas. This chapter focuses on urban development in Phuket, Thailand. It looks at urban tourism in Phuket context pre-and post-tsunami to highlight the importance of stakeholder engagement in sustainable development. Phuket is chosen because it is one of the most popular tourist destinations in Thailand. It is essentially an island with the sprawling urban area to compliment the natural, cultural, and historical resources that it has such as beautiful beaches, Phuket old town, entertainment venues, shopping places, etc. Unfortunately, in 2004, Phuket was damaged by the tsunami, destroying many tourism attractions and businesses. The tsunami disaster made a massive impact on people because tourism has become the primary source of income for Phuket people. Hence, post-tsunami, the city was faced with the challenge of not only rebuilding its infra and superstructure but also rebuilding the livelihood of all communities on the island. After the disaster, there was much supports from all sectors, which contributed to the rapid development of Phuket’s tourism industry. Urban tourism, in particular, proliferated in almost all Phuket areas because it plays a critical role in supporting and driving social and economic development. However, urban tourism development has many advantages and disadvantages to the community and country. A lack of engagement with the stakeholders, particularly the local community in urban tourism development, could pose a challenge to sustainable development …